Non-lichenized Cytosporella, including C. fuligomixta sp. nov., and related plant-associated and fungicolous genera are close to foliicolous, lichenized fungi (Ascomycota, Graphidales) - Marcin Piątek; Monika Stryjak-Bogacka; Paweł Czachura (MycoKeys)
The genus Cytosporella includes non-lichenized, plant associated fungi producing eustromatic conidiomata, phialidic conidiophores and hyaline, ellipsoid conidia. Of the 69 names assigned to this genus in Index Fungorum, only three species are associated with sequence data. In this study, a new species: Cytosporella fuligomixta is described based on a strain isolated from the sooty mould community on Quercus robur leaves in Poland. The phylogenetic analyses including sequences of two loci (LSU, mtSSU) showed that Cytosporella species, together with members of four other non-lichenized, plant associated or fungicolous genera, namely Cladosterigma, Neoacrodontiella, Nothoramularia and Vanderaaea, form a sister group to lichenized and lichenicolous fungi from the family Gomphillaceae and order Graphidales. Previously, Cladosterigma was resolved as a member of Gomphillaceae using multi-locus (mtSSU, SSU, LSU, ITS, rpb2, tef1) and two-locus (LSU, mtSSU) sequence analyses, while Cytosporella, Neoacrodontiella, Nothoramularia were shown to belong to this family using LSU sequence analyses. However, none of them resolved these genera as a sister group to lichenized members of Gomphillaceae. The placement of the genus Vanderaaea within Gomphillaceae is shown here for the first time. Due to phylogenetic, morphological and ecological characteristics a new subfamily Cladosterigmoideae is described for these five non-lichenized genera.